Bioactive properties of powdered peppermint and spearmint extracts: Inhibition of key enzymes linked to hypertension and type 2 diabetes - Cam, Mustafa; Basyigit, Bulent; Alasalvar, Hamza; Yilmaztekin, Murat; Ahhmed, Abdulatef; Sagdic, Osman; Konca, Yusuf; Telci, Isa (ELSEVIER, 2020)
Peppermint and spearmint, both members of the Lamiaceae family, have been used in the form of extracts, infusions, and decoctions, because of their health benefits. Consumers are looking for functional food products which not only provide health benefits but also necessitate less preparation time. Therefore, this study aimed to investigate the bioactive properties of powdered peppermint and spearmint extracts. Peppermint and spearmint extracts obtained using pressurized water extraction were made into powder forms with a spray dryer using the air inlet temperature of 140 degrees C. Powdered peppermint extract (PPE) and powdered spearmint extract (PSE) showed significant inhibition against key enzymes of type 2 diabetes (alpha-glucosidase) and hypertension (angiotensin 1-converting enzyme, ACE). Alpha glucosidase inhibition degree of PPE and PSE as IC50 values was 0.6 and 1.2 mg/mL, respectively, while IC50 values for the ACE inhibition test were 4.5 mg for PPE and 5.8 mg for PSE. The HPLC-DAD method for ACE inhibition activity showed the suitability of this method for plant extracts high in phenolics which had no interference effects on the results. There were no differences between PPE and PSE in the DPPH test. However, PPE had higher Trolox equivalent antioxidant capacity (190 mg/g) with the ABTS test than PSE (170 mg/g). The predominant phenolics of PPE and PSE were found to be eriocitrin (47 mg/g) and rosmarinic acid (27 mg/g), respectively.
Keywords: Mentha piperita; Mentha spicata; Alpha-glucosidase; Angiotensin 1-converting enzyme; Eriocitrin; Rosmarinic acid; PHENOLIC-COMPOUNDS; ANTIOXIDANT CAPACITY; WATER EXTRACTION; BROWN SEAWEEDS; ALPHA-AMYLASE; ACE; GLUCOSIDASE; LAMIACEAE; DISEASE; PROFILE; Food Science & Technology